2019
DOI: 10.1177/0300060519862460
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid and plasma levels of milk fat globule–epidermal growth factor 8 are inversely correlated with radiographic severity of knee osteoarthritis

Abstract: Objective Mounting evidence demonstrates that inflammation plays an important role in the pathogenesis of osteoarthritis (OA). Milk fat globule–epidermal growth factor 8 (MFG-E8) is an important glycoprotein that is involved in anti-inflammatory responses. The present study was performed to assess the MFG-E8 levels in plasma and synovial fluid and explore the association between radiographic severity and MFG-E8 levels in patients with knee OA. Methods This study involved 138 healthy controls and 142 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Tests showed that MFG-E8 can reprogram macrophages to the anti-inflammatory M2 phenotype, relieve apoptosis, reverse cellular oxidative stress and modulate the balance between osteoblasts and osteoclasts 17 19 . Moreover, it is reported that MFG-E8 is significantly downregulated in synovial fluid and plasma in OA patients 20 . Nevertheless, the effects of MFG-E8 in OA remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Tests showed that MFG-E8 can reprogram macrophages to the anti-inflammatory M2 phenotype, relieve apoptosis, reverse cellular oxidative stress and modulate the balance between osteoblasts and osteoclasts 17 19 . Moreover, it is reported that MFG-E8 is significantly downregulated in synovial fluid and plasma in OA patients 20 . Nevertheless, the effects of MFG-E8 in OA remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is uncertain whether MFG-E8 is expressed in the serum of septic patients. MFG-E8 is highly appreciated in inflammatory diseases, including sepsis, colitis, ischaemia and reperfusion-induced intestinal injuries, for its scavenging role and anti-inflammatory properties 7 9 . MFG-E8 performs an anti-inflammatory function mainly by enhancing the clearance of apoptotic cells, but the other mechanisms associated with its role have not been clearly revealed 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%